DEVELOPMENT OF SOFTWARE TOOLS FOR PREPROCESSING COMPUTER TOMOGRAPHY IMAGES - Nigora Sodikova (Web of Journals Publishing, 2025)
This article discusses the key aspects of developing software tools for preprocessing computed tomography (CT) images. CT images play a significant role in medical diagnostics, and preprocessing is essential to improve their quality and ensure accurate analysis. Software tools are used to enhance images, reduce noise, increase contrast, and obtain more precise results. The article covers various image processing methods, algorithms, and technical aspects of developing software tools for this purpose.
Keywords: Computed tomography, image processing, software tools, noise reduction, image enhancement, medical diagnostics, algorithms, image analysis.